2016
DOI: 10.1016/j.reprotox.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposures of lithium and homocysteine and folate protection affect lipid metabolism during mouse cardiogenesis and placentation

Abstract: Embryonic exposures can increase the risk of congenital cardiac birth defects and adult disease. The present study identifies the predominant pathways modulated by an acute embryonic mouse exposure during gastrulation to lithium or homocysteine that induces cardiac defects. High dose periconceptional folate supplementation normalized development. Microarray bioinformatic analysis of gene expression demonstrated that primarily lipid metabolism is altered after the acute exposures. The lipid-related modulation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…With maternal diabetes or alcohol use, offspring display a higher incidence of CHDs than present in the normal population, as do offspring in pregnancies associated with maternal obesity. In our recent study on acute Li + and HCy exposure resulting in abnormal cardiac and placental physiology, we noted that lipid metabolism was altered in those developing organs and normal physiology and lipid metabolism were protected with FA supplementation (Han et al, ). We propose that fetoplacental dyslipidemia may be a common factor in the development of CHDs, including with alcohol exposure that can be prevented with periconceptional folate supplementation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With maternal diabetes or alcohol use, offspring display a higher incidence of CHDs than present in the normal population, as do offspring in pregnancies associated with maternal obesity. In our recent study on acute Li + and HCy exposure resulting in abnormal cardiac and placental physiology, we noted that lipid metabolism was altered in those developing organs and normal physiology and lipid metabolism were protected with FA supplementation (Han et al, ). We propose that fetoplacental dyslipidemia may be a common factor in the development of CHDs, including with alcohol exposure that can be prevented with periconceptional folate supplementation.…”
Section: Discussionmentioning
confidence: 98%
“…There are several hypotheses for how alcohol disrupts development, and many mechanisms have been implicated, including effects on lipid metabolism, zinc, lipid rafts, L1 cell adhesion molecule, alcohol dehydrogenase, and catalase (Lindi et al, 2001;Goodlett et al, 2005). We previously provided evidence that lithium (Li 1 ), homocysteine (HCy), and alcohol exposure all induce similar cardiac and placental defects that can be prevented by FA supplementation (Serrano et al, 2007(Serrano et al, , 2010Han et al, 2009), and because we recently demonstrated that Li1 and HCy exposure altered lipid metabolism in abnormally developing hearts and placentas (Han et al, 2016), our present hypothesis is that embryonic alcohol exposure alters lipid metabolism and lipid related gene expression, as well as genes associated with the FA cycle ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that dietary folic acid (FA) supplementation can prevent cardiac and neural defects during embryo development . The cardiac defects induced by ethanol, lithium, and selenium have been reported to be rescued by FA supplement in mice, chicken, and zebrafish embryos . Our previous observations suggested that EOM from PM2.5 induced heart defects in zebrafish embryos, which could be prevented either by CH223191 (an AhR inhibitor) or by CHIR99021 (a Wnt activator).…”
Section: Introductionmentioning
confidence: 99%
“…Daily administration of FA can significantly decrease homocysteine levels therefore, FA supplementation can significantly reduce cardiovascular risk . There are many reports indicated the cardiac defects induced by ethanol, lithium, and selenium in mice, chicken, and zebrafish embryos have been rescued by feeding FA supplement …”
Section: Introductionmentioning
confidence: 99%